FEATURES OF THE INTERRELATIONSHIP OF PERIODONTAL DISEASES AND SOMATIC DISEASES (LITERATURE REVIEW) - M.Y. Vasko; I.M. Tkachenko (Український стоматологічний альманах, 2023)
The interrelationship of periodontal diseases and somatic diseases has a two-way aggravating character.